Syarat Cukup Ketaksamaan Holder di Ruang Lebesgue dengan Variabel Eksponen - Ba'is, Mohamad Abdul; Rahman, Hairur; Herawati, Erna (Jurnal Riset Mahasiswa Matematika, 2022)
Hӧlder inequality is a basic inequality in functional analysis. The inequality used for proofing other inequalities. In this research, the development of the application of the Hӧlder inequality in the Lebesgue spaces with variable exponent and Morrey spaces with variable exponent. The integral Hӧlder inequality is used because the Lebesgue spaces with variable exponent and Morrey spaces with variable exponent is a function space.This research shows the sufficient condition of Hӧlder inequality in Lebesgue spaces with variable exponent and the Morrey spaces with variable exponent according to the norm of the function and its characteristics.